Kontruksi Sosial Tentang Gender Pada Koki Solaria Royal Plaza Surabaya - Aura Syari Husna (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
This study aims to analyze the social construction of gender roles in professional kitchens, specifically in Solaria Restaurant, Royal Plaza Surabaya. In the workplace, the division of roles based on gender is often influenced by ingrained social norms and values. This phenomenon is evident in the culinary industry, where men often occupy strategic roles as head chefs, while women are relegated to supportive positions. Using a qualitative approach, this study employs Berger & Luckmann’s (1966) social construction theory and Judith Butler’s (1990) theory of gender performativity. Data were collected through in-depth interviews with male and female chefs and kitchen managers, as well as participatory observations in the restaurant's kitchen. The findings reveal that social construction significantly influences task allocation in Solaria‟s kitchen. Male chefs are often entrusted with strategic responsibilities requiring decision-making, whereas female chefs are assigned ‘lighter’ tasks. These gender stereotypes reflect deep-rooted structural biases in the professional kitchen culture. Moreover, workplace dynamics show a gender hierarchy where male chefs wield greater authority in workplace interactions. This study recommends that restaurant management eliminate gender bias in task allocation through skill-oriented assessments. Such measures are expected to create a fairer and more inclusive work environment.